An Ultrathin, Fast-Response, Large-Scale Liquid-Crystal-Facilitated Multi-Functional Reconfigurable Metasurface for Comprehensive Wavefront Modulation - Wu, Xin Yu (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.